In vivo binding by Arabidopsis SPLICING FACTOR 1 shifts 3′ splice-site choice, regulating circadian rhythms and immunity in plants - Yamila Carla Agrofoglio; María José Iglesias; María José de Leone; Carlos Esteban Hernando; Martin Lewinski; Sol Belén Torres; Giuliana Contino; Kim Joelle Köhnke; Marcelo Javier Yanovsky; Dorothee Staiger; Julieta Lisa Mateos (Proceedings of the National Academy of Sciences, 2026)
Alternative splicing expands proteome diversity and enables phenotypic plasticity across eukaryotes. In plants, mutations in spliceosomal components impair development and stress responses, but the molecular mechanisms remain unclear. Here, we define the molecular function of SPLICING FACTOR 1 (AtSF1) in Arabidopsis thaliana using individual-nucleotide resolution UV crosslinking and immunoprecipitation combined with RNA sequencing of sf1 mutants. We identify the in vivo branch point sequences bound by AtSF1 and delineate its RNA-binding landscape, revealing pervasive splicing defects dominated by aberrant 3′ splice-site selection. Structural comparison with human SF1 indicates that AtSF1 retains branch point recognition capacity but features a distinct domain organization, including a restructured C-terminal region absent in metazoans, suggesting a divergent RNA-binding mode that evolved to meet plant-specific splicing demands. AtSF1 targets are enriched for core circadian clock and defense genes, consistent with the long-period phenotype and immune-compromised phenotypes of sf1 mutants. Together, these findings establish that AtSF1 orchestrates alternative 3′ splice-site choice through intron binding and branch point recognition, coupling RNA processing with circadian and immune regulation in plants.